New strategies to improve clinical outcomes for diabetic kidney disease - Forst, Thomas; Mathieu, Chantal; Giorgino, Francesco; Wheeler, David C.; Papanas, Nikolaos; Schmieder, Roland E.; Halabi, Atef; Schnell, Oliver; Streckbein, Marina; Tuttle, Katherine R. (BMC medicine, 2022)
Background Diabetic kidney disease (DKD), the most common cause of kidney failure and end-stage kidney disease worldwide, will develop in almost half of all people with type 2 diabetes. With the incidence of type 2 diabetes continuing to increase, early detection and management of DKD is of great clinical importance. Main body This review provides a comprehensive clinical update for DKD in people with type 2 diabetes, with a special focus on new treatment modalities. The traditional strategies for prevention and treatment of DKD, i.e., glycemic control and blood pressure management, have only modest effects on minimizing glomerular filtration rate decline or progression to end-stage kidney disease. While cardiovascular outcome trials of SGLT-2i show a positive effect of SGLT-2i on several kidney disease-related endpoints, the effect of GLP-1 RA on kidney-disease endpoints other than reduced albuminuria remain to be established. Non-steroidal mineralocorticoid receptor antagonists also evoke cardiovascular and kidney protective effects. Conclusion With these new agents and the promise of additional agents under clinical development, clinicians will be more able to personalize treatment of DKD in patients with type 2 diabetes. Keywords: Type 2 diabetes, Diabetic kidney disease, Kidney protective agents